Common-Sense Rejected by Physicists: : A Level-Headed Approach to Time and Quantum Weirdness - Boyd, Jeffrey (JOURNAL OF ADVANCES IN PHYSICS, 2021)
We propose a new integration of relativity and quantum mechanics (QM). Your cell phone or smart phone is a rich source of empirical information about relativity. It tells time based on a system called Coordinated Universal Time (UTC) which assumes absolute simultaneity: all observers in all inertial frames observe the same sequence of all events. You must choose whether to trust the time on your cell phone, or trust Einstein’s incompatible ideas about a space-time continuum. As concerns QM, the existence of “weirdness” means a mistake was made in QM’s starting assumptions. This article finds and corrects that mistake and presents for the first time, a quantum world free of all weirdness. There is another half to nature, previously unrecognized. It is devoid of energy and matter, namely zero-energy Elementary Waves which move within the medium of aether. We derive the linear wave PDE’s. There is evidence that Elementary Waves are in control of nature, despite their lack of energy. The existence of UFO’s (Unidentified Flying Objects) suggests that someone has learned how to control Elementary Waves. If we could learn from the UFO’s, we might acquire a decisive advantage in our battle against climate change.